Reverse chemical ecology indicates long-chain aldehydes as new potential semiochemicals for the African elephant Loxodonta africana - Zaremska, Valeriia; Chidhambaram, Manikkaraja; Archunan, Govindaraju; Knoll, Wolfgang; Pelosi, Paolo (Frontiers in Ecology and Evolution, 2022)
Chemical communication between sexes in the elephants has been well studied at the chemical and behavioural levels, but little is known about the proteins mediating the exchange of chemical signals. Two sex pheromones have been identified in Asian elephants: (Z)-7-dodecenyl acetate and frontalin, and their effects on the elephants’ behaviour have been described in detail. The genomes of both the Asian (Elephas maximus) and the African elephant (Loxodonta africana) have been poorly annotated. In particular, the complete sequences of two odorant-binding proteins and a VEG protein are available for the African elephant, together with isoforms and other members of the same families, which however are incomplete or unreliable. In a previous study, we have expressed the OBP1 of both elephant species, and investigated their binding properties. We showed that OBP1 is tuned to the pheromone (Z)-7-dodecenyl acetate and few structurally related linear esters, but also binds (E)-β-farnesene and farnesol with good affinity. In this work we have explored the characteristics of the second OBP of the African elephant (LafrOBP2). This protein, which was not found in the trunk wash, does not bind any of the above listed semiochemicals. Instead, it shows selected affinity to unsaturated linear aldehydes of 16 carbon atoms, specifically (Z)-9-hexadecenal, (Z)-11-hexadecenal and (10E,12Z)-hexadecadienal (bombykal). Fourteen and 18 carbon orthologues show only much reduced binding affinity. Some linear alcohols, fatty acids and esters also weakly bind this protein with dissociation constants about one order of magnitude higher.